The Effects of Minecraft Videogame On Creativity - Fauzan, Norsiah; sophian Shminan, Ahmad; James Anak Binit, Aquailla; ., . (International Journal of Engineering and Technology, 2018)
The aim of this research is find out the effects of minecraft videogames on creativity. Eight undergraduates were assigned to experimental group and control group for recording of the brainwaves while playing minecraft video games and other videos. The results showed that the average of brain waves from different sub-bands for Minecraft games is higher than other games. The dominant of delta waves at Fp1 & Fp2 showed that the subjects are paying high attention and improved their decision-making levels. High T3 & T4 on Alpha( Minecraft's)wave indicates that it stimulates the brain to activate both parts of the brain. The results showed that Minecraft is able to increase high-level thinking. The core cognitive mechanism during playing minecraft video games was the attention network collectively referred as fronto-parietal attentional control network. This is indicated as sub-network known as executive control network, default mode network and salient network in the previous research.